The Laws of the Earliest English Kings / edited and translated [by] F. L. Attenborough. - Attenborough, F. L. (Frederick Levi), 1887-; Attenborough, F. L. (Frederick Levi), 1887- (Cambridge Library Collection - Medieval History., 2015)
Frederick Levi Attenborough (1887-1973) studied at Cambridge and was a Fellow of Emmanuel College between 1920 and 1925. He later became the Principal of University College, Leicester. In 1922 Cambridge University Press published his edition of the early Anglo-Saxon laws, with a facing-page modern English translation. A few years earlier, Felix Lieberman had published his monumental three-volume Die Gesetze der Angelsachsen, which is still the definitive specialist edition of the laws (as Attenborough rightly predicted), and which is also reissued in the Cambridge Library Collection. Attenborough explains that his work is for social and legal historians who do not read German, or do not require the full critical apparatus and contextual material provided by Lieberman. Attenborough's book covers the laws from Aethelbert to Aethelstan; in 1925 Cambridge published a continuation by Agnes Robertson, The Laws of the Kings of England from Edmund to Henry I, which is also available.